1997
DOI: 10.1111/j.1699-0463.1997.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

The homogeneity of hidradenitis suppurativa lesions

Abstract: Recent data suggest that hidradenitis suppurativa is a disease of the follicle, but the histological homogeneity of findings over time and in different anatomical regions has not been verified. Its description may help towards a better classification of the follicular diseases. Correct classification provides both knowledge by interference and a way of generalizing with respect to the significance of specific findings. The intra‐individual variation of hidradenitis was described through classification of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 2 publications
5
16
0
1
Order By: Relevance
“…Extrusion of follicular contents into the dermis produces an influx of neutrophils, lymphocytes and histiocytes leading to abscess formation [6,7]. In a histological study, eccrine involvement was seen more often than apocrine involvement [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Extrusion of follicular contents into the dermis produces an influx of neutrophils, lymphocytes and histiocytes leading to abscess formation [6,7]. In a histological study, eccrine involvement was seen more often than apocrine involvement [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified the hair follicle as the core element of hidradenitis, prompting some authors to suggest that the disease be renamed acne inversa, although substantial differences exist between the 2 diseases [1,3,4,5,6]. Ultrasound investigations have shown hair follicles to be dilated in the non-involved perilesional skin of hidradenitis patients, while histological studies have found signs of follicular plugging and dilated, cyst-like hair follicles, as well as the absence of lymphadenopathy [4,5,6,7,8,9,10]. In more developed lesions, the inflammatory infiltrate appears centred on the hair follicle, most often sparing any adjacent apocrine glands.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory diseases which respond to dapsone are almost invariably associated with the infiltration of large numbers of polymorphonuclear leucocytes into the affected tissue, and it appears that neutrophils and neutrophil products are the major targets for this drug [18]. The late appearance of neutrophils in the lesions of HS may therefore partly explain the limited success of this treatment [19,20,21,22]. …”
Section: Discussionmentioning
confidence: 99%